How to overcome challenging iliac artery anatomy in endovascular repair for AAA - Wortmann, Markus; Bischoff, Moritz; Hakimi, Maani; Böckler, Dittmar (The journal of cardiovascular surgery, 2018)
Challenging iliac anatomy is a major limitation of endovascular repair for aortic aneurysms. Stenotic lesions, excessive calcification, tortuosity, and aneurysmal dilatation jeopardize technical success of device implantation and long-term success. This review addresses technical options in treating patients with stenotic or aneurysmatic iliac arteries. Endovascular solutions and hybrid procedures are included to demonstrate the wide scope of endovascular therapy that may be offered to patients with unfavorable iliac anatomy.
Gesehen am 03.04.2020